Real-world experience with the cusp-overlap deployment technique in transcatheter aortic valve replacement: A propensity-matched analysis - Maier, Oliver; Piayda, Kerstin; Binnebößel, Stephan; Berisha, Nora; Afzal, Shazia; Polzin, Amin; Klein, Kathrin; Westenfeld, Ralf; Horn, Patrick; Jung, Christian; Kelm, Malte; Veulemans, Verena; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background The implantation depth (ID) is a critical condition for optimal hemodynamic and clinical outcomes in transcatheter aortic valve replacement (TAVR). The recently recommended cusp-overlap technique (COT) offers optimized fluoroscopic projections facilitating a precise ID. This single-center observational study aimed to investigate short-term clinical performance, safety, and efficacy outcomes in patients undergoing TAVR with self-expandable prostheses and application of COT in a real-world setting. Materials and methods From September 2020 to April 2021, a total of 170 patients underwent TAVR with self-expandable devices and the application of COT, while 589 patients were treated from January 2016 to August 2020 with a conventional three-cusp coplanar view approach. The final ID and 30-day outcomes were compared after 1:1 propensity score matching, resulting in 150 patients in both cohorts. Results The mean ID was significantly reduced in the COT cohort (−4.2 ± 2.7 vs. −4.9 ± 2.3 mm; p = 0.007) with an improvement of ID symmetry of less than 2 mm difference below the annular plane (47.3 vs. 57.3%; p = 0.083). The rate of new permanent pacemaker implantation (PPI) following TAVR was effectively reduced (8.0 vs. 16.8%; p = 0.028). While the fluoroscopy time decreased (18.4 ± 7.6 vs. 19.8 ± 7.6 min; p = 0.023), the dose area product increased in the COT group (4951 ± 3662 vs. 3875 ± 2775 Gy × cm2; p = 0.005). Patients implanted with COT had a shorter length of in-hospital stay (8.4 ± 4.0 vs. 10.3 ± 6.7 days; p = 0.007). Conclusion Transcatheter aortic valve replacement using the cusp-overlap deployment technique is associated with an optimized implantation depth, leading to fewer permanent conduction disturbances. However, our in-depth analysis showed for the first time an increase of radiation dose due to extreme angulations of the gantry to obtain the cusp-overlap view.